2016
DOI: 10.5489/cuaj.3220
|View full text |Cite
|
Sign up to set email alerts
|

Post-radiation epithelioid angiosarcoma of the urinary bladder and prostate

Abstract: Angiosarcoma of the lower urinary tract is exceedingly rare. A minority of cases are associated with local radiotherapy. Epithelioid angiosarcoma is a variant of angiosarcoma composed of large rounded epithelioid endothelial cells that are positive for cytokeratin on immunostaining. There are only two cases of post-radiation epithelioid angiosarcoma reported in the urinary bladder, and none in the prostate gland. We report a case of epithelioid angiosarcoma involving the urinary bladder and prostate in a patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…MYC gene amplification is often observed in radiation-associated angiosarcomas and only rarely in de novo angiosarcomas [ 13 , 22 ]. Immunohistochemistry was shown to be a useful surrogate marker for MYC amplification in post-radiation angiosarcoma after treatment for breast carcinomas [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MYC gene amplification is often observed in radiation-associated angiosarcomas and only rarely in de novo angiosarcomas [ 13 , 22 ]. Immunohistochemistry was shown to be a useful surrogate marker for MYC amplification in post-radiation angiosarcoma after treatment for breast carcinomas [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even within these entities, angiosarcoma of the urinary bladder is an uncommon diagnosis. First described in 1907 by Jungano [ 3 ], only a few cases of angiosarcoma primary to the bladder have been reported so far, most of which associated with previous pelvic radiotherapy ( Table 1 ) [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Given its biologically aggressive phenotype, prognosis is dismal, with a five-year survival rate between 10% and 35% and common causes of death being local recurrence and distant metastases [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Awareness in the variability of the morphological aspects in a bladder angiosarcoma is very important, as features can be misleading, especially in small biopsy specimens, a situation that initially occurred in our current case. The most important feature of this tumor is blood-filled vascular channels lined by malignant endothelial cells as seen in "classical angiosarcomas", but solid architecture with spindle cells or even a predominant epithelioid morphology may be encountered [1][2][3]9]. Therefore, one must keep in mind the main differential diagnosis of angiosarcomas, (hemangioma, Kaposi's sarcoma, poorly differentiated or sarcomatoid urothelial carcinoma and metastatic melanoma) and use appropriate immunohistochemical panel of stains to make the correct diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that sarcomas increase their incidence after radiotherapy for prostate carcinoma, being 6% within the radiation field and 2% outside the radiation field ( 11 ). In this regard, few cases of angiosarcoma have been reported following radiotherapy for carcinoma of the prostate ( 12 16 ). To the best of our knowledge we describe the first two cases of intra-abdominal angiosarcomas secondary to radiotherapy treatment for prostate carcinoma.…”
Section: Discussionmentioning
confidence: 99%